Tipologi Aplikasi Infrastruktur Hijau Skala Komunitas pada Kampung Kota di Indonesia - Al Faraby, Jimly; Asa Aulia Trisedya, Rizky; Realino Justin Novandri Priambudi, Bernardinus; Zahra Pramesti, Alifia (Jurnal Lanskap Indonesia, 2024)
This paper addresses one of the knowledge gaps that exists in green infrastructure (GI) discourses, that is the lack of understanding on the application of GI at community scale. GI was first introduced as an alternative to address problems caused by rapid urbanisation. Recently, GI has become a crucial part of strategies to achieve sustainable development and therefore has been widely advocated for its environmental, social, and economic benefits. Although the concepts and benefits of green infrastructure have been widely discussed and recognized in the literature, much of the discussions on GI tend to revolve around its applications at the city and regional scales, while the application of small scale GI at the community level has not been much explored, despite the importance of multiscale principle in the application of GI. To address that issue, this study focuses on the application of small-scale GI at the community level. It employed a systematic review to analyse publications, including articles published in scientific journals and news on reliable mass media on the internet, regarding the application of small-scale GI in 23 Indonesian urban kampung. The study shows that in dense settlements like urban kampung, community scale GI emerges as an alternative solution to the lack of space for GI development. From the 23 cases analysed, GI is mostly intended to function as a mean for environmental conservation and to promote food security.